Vibrational spectroscopic study of two dimensional polymer compounds of pyrazinamide - Andreeva, Liljana; Minceva Sukarova, Biljana; Başar, Gönül; AKYÜZ, SEVİM (Elsevier, 2007)
In this study, the Raman and far-IR spectra of the two dimensional coordination polymer compounds, M(PZA)2Ni(CN)4 {where M = Mn, Ni, Zn or Cd; PZA = pyrazinamide} and mid-IR spectrum of Zn(PZA)2Ni(CN)4 were reported for the first time. Far-IR spectroscopic study allowed us to make correction in the bonding mode of PZA. PZA molecules are found to involve coordination through one of the pyrazine ring nitrogen atoms. The spectral features suggest that the compounds are similar in structure to the Hofmann type two dimensional coordination polymer compounds, formed with Ni (CN)4-2? ions bridged by M(PZA)2+2? cations. Vibrational bands originated from both PZA and Ni(CN)4 group were assigned.
Keywords: Infrared; Far infrared and Raman spectra; Hofmann type complexes; Tetracyanonickelate; Transition metal; Pyrazinamide; Pyrazine carboxamide